Effect of dose of chlorate on growth performance of nursery pigs - T E Burkey; J Ernest Minton; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
A 14-day growth study was conducted to evaluate the effects of feeding varied levels of chlorate on weanling pig growth performance. A previous experiment with weanling pigs fed diets containing added chlorate (800 ppm) resulted in numerical decreases in ADG, ADFI and F/G as compared to diets with no added antimicrobial, a commonly used antimicrobial (carbadox), or another feed additive, mannanoliogsaccharide. The negative effects of feeding 800 ppm chlorate were confirmed in this study. Additionally, the current trial demonstrated that pigs fed diets containing 200 ppm sodium chlorate had greater ADG, ADFI, and d 14 average weights than pigs fed diets containing 800 ppm sodium chlorate and numerically greater ADG and ADFI than those fed diets without chlorate.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Sodium Chlorate; Antimicrobials; Weanling Pigs; Swine